2022
DOI: 10.1155/2022/6803154
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of CXCL10/CXCR3 in Ventilator-Induced Lung Injury Caused by High Mechanical Power

Abstract: Background. The energy delivered by a ventilator to the respiratory system in one minute is defined as mechanical power (MP). However, the effect of ventilator-induced lung injury (VILI) in patients suffering from acute respiratory distress syndrome (ARDS) is still unknown. Our previous studies revealed that CXCL10 may be a potential biomarker of lung injury in ARDS. Therefore, the aim of this study was to compare the lung injury of rats and patients under different MP conditions to explore the involvement of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…CXCL10 promoted the occurrence and development of lung injury by binding to CXCR3 [ 23 ]. In addition, in our previous study, it was confirmed that the level of CXCL10 increased significantly in ARDS patients and the enhanced inflammatory response promoted the progression of lung injury [ 24 ]. Therefore, it was suggested that the CXCL10/CXCR3 pathway might play an important role in the mechanism of lung injury during endogenous ARDS.…”
Section: Discussionmentioning
confidence: 66%
“…CXCL10 promoted the occurrence and development of lung injury by binding to CXCR3 [ 23 ]. In addition, in our previous study, it was confirmed that the level of CXCL10 increased significantly in ARDS patients and the enhanced inflammatory response promoted the progression of lung injury [ 24 ]. Therefore, it was suggested that the CXCL10/CXCR3 pathway might play an important role in the mechanism of lung injury during endogenous ARDS.…”
Section: Discussionmentioning
confidence: 66%
“…The MP represents the energy delivered to the respiratory system by mechanical ventilation, which results from a combination of ventilatory variables. Therefore, MP might have a higher predictive value for patient-centered outcomes, as different combinations of its components may yield a similar damage to the lung [ 4 - 8 ]. The ability to combine the effect of time-varying ventilatory variables seems particularly attractive in spontaneously breathing patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we showed that early PP may reduce MP WAL while improving oxygenation and CO2 clearance during NIV. Therefore, early PP therapy may be a more “energetically” advantageous strategy to relieve hypoxemia than PEEP uptitration, which may overdistend the lung and increase MP and lung injury when it does not recruit atelectatic lung tissue [ 8 , 35 ]. The association of PEEP levels and NIV duration with COVID-19 pneumonia severity and mortality is consistent with this view [ 11 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xie Y et al [40], comparó la LPIV en diferentes condiciones de PM, para explorar la participación del receptor de quimiocinas Cxcl10/Cxcr3. Se dividieron en 2 grupos, PM elevada y baja.…”
Section: Pm Lpiv Y Mortalidad Evidencia Clínicaunclassified